The Essence of the Prohibition of Tender Rigging from a Business Competition Law Perspective - Dave David Tedjokusumo; Lucianus Budi Kagramanto; Endang Prasetyawati; Krisnadi Nasution (Batulis Civil Law Review)
Introduction: The government has made efforts to ensure that existing business competition legal regulations can accommodate the broad legal needs of society, but in reality, in everyday life, legal problems are still often encountered. One of the fundamental legal issues related to business competition in Indonesia is regarding government procurement of goods/services. There are many practices of bid rigging in the process of procuring government goods/services to determine the winner in a tender. Tender conspiracy cases often occur in Indonesia, therefore everything related to tender conspiracy must be carefully scrutinized.